Motor Pattern Selection via Inhibition of Parallel Pathways - Blitz, Dawn M. (J Neurosci, 1997)
Motor pattern selection from a multifunctional neural network often results from direct synaptic and modulatory actions of different projection neurons onto neural network components. Less well documented is the presence and function of interactions among distinct projection neurons innervating the same network. In the stomatogastric nervous system of the crab Cancer borealis, several distinct projection neurons that influence the pyloric and gastric mill rhythms have been studied. These rhythms are generated by overlapping subsets of identified neurons in the stomatogastric ganglion (STG). One of these identified projection neurons is the modulatory proctolin neuron (MPN). We showed previously that MPN stimulation excites the pyloric rhythm by its excitatory actions on STG neurons. In contrast to its excitatory actions on the pyloric rhythm, we have now found that MPN inhibits the gastric mill rhythm. This inhibition does not occur within the STG, but instead results from MPN-mediated inhibition of two previously identified projection neurons within the commissural ganglia. These projection neurons innervate the STG and, via their actions on STG neurons, they elicit the gastric mill rhythm as well as modify the pyloric rhythm in a manner distinct from MPN. By inhibiting these projection neurons, MPN removes excitatory drive to gastric mill neurons and elicits an MPN-specific pyloric rhythm. Motor pattern selection by MPN therefore results from both a direct modulation of STG network activity and an inhibition of competing pathways.